Individuals Greed and Capitalism in Film Killers of the Flower Moon (2023) - Inelsa, Violeta; Wantasen, Isnawati Lydia; Saputra, Buyung Ade; Cowell, Dustin (Journal of English Language Teaching, Linguistics, and Literature Studies, 2025)
This research investigates the themes of individual greed and capitalism as portrayed in Martin Scorsese’s film Killers of the Flower Moon (2023). The film chronicles the exploitation of the Osage people in the 1920s, following the discovery of oil on their land. The study aims to explore how greed reflects and perpetuates the capitalist system. Specifically, it analyzes the representation of capitalism in the film through both narrative and cinematic devices. To achieve this objective, a qualitative descriptive method was employed. The analysis included repeated viewings of the film, documentation through screenshots, and an extensive review of relevant literature. This approach was grounded in Marxist theory and the literary framework established by Wellek and Warren. The findings highlight illustration of the interconnection between individual greed and capitalist structures. These findings suggest that the film portrays capitalism not merely as an economic system but also as a mechanism of social exploitation. Within this context, the accumulation of wealth is depicted as being achieved through manipulation, violence, and systemic injustice against marginalized communities. The significance of this study lies in its contributions to the fields of literary and film studies. It illustrates how cinema can reflect and critique the workings of capitalism while offering valuable insights into issues of social inequality. This research serves as a critical reference point for future inquiries in Marxist literary criticism and cultural analysis, informing subsequent critical readings of films that tackle similar themes.Keywords:     Capitalism, Greed, Exploitation, Killers of the Flower Moon